Repair of Vesicovaginal FistulA: Experiene of 30 Cases and Analysis of Outcome Predictors (Bangladesh Journal of Urology, 2020)
Objective:To find out the predictors of outcome of vesicovaginal fistula repair.Method: From 2013 t0 2015,thirty patients with vvf from different hospitals were managed surgically by different approach by single surgeons. During evaluation patients records,the duration of vvf,time of surgical repairs,site of fistulas, positionof fistulas,approach of repairs,ureteric stenting,and catheteruzation were considered. A univariate analysis was used to assess individual variables, by the chi - squared test andsignificant variables found in univariate analysis were considered in a mulivariate analysis.Result: Among 30 cases 90% were successful repair. We consider the following variables to be important risk factors like history of previous repair,timeof surgery,site of fistulas and surgical approach.Conclusion: Earlier correction of vvf, abdominal approach,high variety and primary repair has good outcome.Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.136-140